Lingvoculturological Study and Classification of The Term Tolerance (Texas Journal of Philology, Culture and History, 2023)
Today, the issue of tolerance has acquired particular relevance - tolerance for people belonging to different nationalities and cultures. Recently, this problem has acquired particular importance because more and more often we began to notice manifestations of hostility, unfriendliness, anger, and aggressiveness. Moods of mutual intolerance and cultural selfishness penetrate the family and the school. Such trends negatively affect the development of the personality of children, their spirituality and kindness. That is why parents need to carefully consider the education of children's tolerance and find effective mechanisms that contribute to its formation